Usage of Online Learning Resources among Academic Staff at a Malaysian University - Radin Salim, Kamilah; Abdullah, Morina; Liza Ali, Nor; Ali, Rosmah (International Journal of Engineering and Technology, 2018)
This paper reports on the awareness and usage of online learning resources in teaching and learning among the academic staff at a public university in Malaysia. In addition, the advantages and disadvantages of online learning resources are also presented. Online learning resources recommended by the management of the university include e-learning modules, Open Courseware (OCW), Massive Open Online Courses (MOOC), BLOSSOMS, Edutainment and Video of Exemplary Professionals. Data were collected using a survey questionnaire with Likert scale items and open-ended questions. The questionnaires were distributed to 160 academic staff of the university. The results show that the most attended training was e-learning and most respondents are currently implementing it in their courses. However, less than 10% of the respondents implemented the OCW, MOOC, BLOSSOMS and Edutainment. About 23.1% of the respondents implemented Video of Exemplary Professionals in their teaching and learning. Some respondents also reported lack of student participation in using e-learning and other resources due to system instability. The practical implication of this study is that more training on new online learning resources should be provided to the academic staff to increase their skills in using the online learning resources in their teaching. Better internet connection is also necessary to boost the use of these resources.Â